MAIN CAUSES OF GRAVITATION PROCESSES WITHIN THE MIDDLE DNIEPER REGION - Ivanik, O.; Tustanovska, L.; Hadiatska, K. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Integrated assessment and analyses of gravitational geological processes impact on the technogene objects is based on a systematic approach to the analysis of the geological environment; creation of geological, mathematical and spatial models of the geological environment, development of analytical tools. The complex application of geological and geomorphological methods (structural-morphometric analysis, comparative tectonics and structural analysis), remote sensing data and GIS technologies made it possible to identify the relationship between the processes of geomorphogenesis and tectogenesis within the Middle Dnieper area, identify the causes of gravitational geological processes, and build a series of spatial models. These models describe the impact of geomorphological and tectonic processes on the natural hazards. Based on the analysis of structural and morphometric indices, the tectonic structures, which are most elevated in relief, were recorded. Using the residual relief map, located above the baseline surfaces of the respective orders, structural zones are highlighted, reflecting the relationship of tectonic and erosion and reservoir erosion processes. Digital models of base surfaces and residual topography are aimed at the detection of local structures and the study of slope processes of the territory. Neotectonic movements of not only local but also regional character were allowed to follow. The residual relief outlines the positive forms of relief confined to anticlinal folds, which refer to the positive anomalies of gravity.